The metabolism and pharmacokinetics of [14C]-S-777469, a new cannabinoid receptor 2 selective agonist, in healthy human subjects - Sekiguchi, Kazutaka; Fukumura, Kazuya; Hasegawa, Hiroshi; Kanazu, Takushi (Xenobiotica, 2015)
Abstract 1. The metabolism and pharmacokinetics of S-777469 were investigated after a single oral administration of [14C]-S-777469 to healthy human subjects. 2. Total radioactivity was rapidly and well absorbed in humans, with Cmax of 11 308 ng eq. of S-777469/ml at 4.0 h. The AUCinf ratio of unchanged S-777469 to total radioactivity was approximately 30%, indicating that S-777469 was extensively metabolized in humans. 3. The metabolite profiling in human plasma showed that S-777469 5-carboxymethyl (5-CA) and S-777469 5-hydroxymethyl (5-HM) were the main circulating metabolites, and the AUCinf ratio of 5-CA and 5-HM to total radioactivity were 24 and 9.1%, respectively. These data suggest that S-777469 was subsequently metabolized to 5-CA in humans although the production amount of 5-CA was extremely low in human hepatocytes. 4. Total radioactivity was mainly excreted via the feces, with 5-CA and 5-HM being the main excretory metabolites in feces and urine. Urinary excretion of 5-CA was comparable with that of 5-HM, whereas fecal excretion of 5-CA was lower than that of 5-HM. 5. In conclusion, the current mass balance study revealed the metabolic and pharmacokinetic properties of S-777469 in humans. These data should be useful to judge whether or not the safety testing of metabolite of S-777469 is necessary.